The Contribution of Education in the Family to Form Muslim Personality Qualified - Ahmad Suradi; Nopian Gustari; Nilawati Nilawati (Jurnal Ilmiah Iqra', 2021)
The Contribution of Education in the Family to Form Muslim Personality Qualified. This article describes about the contribution of education in the family to form muslim personality qualified. The family has an important role in determining the progress of a nation, so they theorize that the family is a very important unit in society. Therefore, all kinds of community depravity is the result of weak family institutions. For a child the family is the first and foremost place for growth and development. The main function of the family is as a vehicle to educate, nurture and socialize children, develop the ability of all its members in order to perform its functions in the community well, and, to provide satisfaction and a healthy environment in order to achieve prosperous family. The family is the earliest and most effective place to run the functions of the education and welfare. If the family fails to teach the truth, the spirit, the desire to be the best, and master the basic abilities. Because the failure of the family in shaping the character of the child will result in the growth of people with bad character or not character.